2017
DOI: 10.3892/ol.2017.7514
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic evaluations of ultrasound and magnetic resonance imaging in mammary duct ectasia and breast cancer

Abstract: The objective of the present study was to evaluate the diagnostic efficiency of ultrasound (US) and magnetic resonance imaging (MRI) in the diagnosis and differential diagnosis of mammary duct ectasia (MDE) and breast cancer. This retrospective study was performed on 35 patients with MDE and 105 patients with breast cancer using US and MRI. Imaging features, semi-quantitative and quantitative parameters were analyzed to determine their diagnostic value for MDE and breast cancer. The average age of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Currently, imaging examination is still the main strategy for early diagnosis of breast cancer, and the two commonly used examination modalities are ultrasound and magnetic resonance imaging (MRI). MRI plain scan can accurately localize the lesion morphology, with the help of dynamic contrast-enhancement (DCE) method, the paramagnetic contrast medium is introduced to get the qualitative curve characteristics and quantitative parameters of contrast penetration and clearance inside the tumor, so that the pathological and physiological behavior is intuitively manifested, with the diagnostic efficacy that has been confirmed in common cancers such as cervical cancer and lung cancer [ 8 , 9 ]. Ultrasonic diffused optical tomography (DOT) is a novel functional imaging system capable of reflecting the morphological information and metabolic status of breast masses to achieve the identification and diagnosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, imaging examination is still the main strategy for early diagnosis of breast cancer, and the two commonly used examination modalities are ultrasound and magnetic resonance imaging (MRI). MRI plain scan can accurately localize the lesion morphology, with the help of dynamic contrast-enhancement (DCE) method, the paramagnetic contrast medium is introduced to get the qualitative curve characteristics and quantitative parameters of contrast penetration and clearance inside the tumor, so that the pathological and physiological behavior is intuitively manifested, with the diagnostic efficacy that has been confirmed in common cancers such as cervical cancer and lung cancer [ 8 , 9 ]. Ultrasonic diffused optical tomography (DOT) is a novel functional imaging system capable of reflecting the morphological information and metabolic status of breast masses to achieve the identification and diagnosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A biopsy is a golden standard for the diagnosis of BC, but some in patients with tiny lesions, it is difficult to obtain biopsy tissue, and biopsy can also lead to paralytic fibrosis or even sclerotic mass of breast tissue [ 5 ]. Imaging studies are generally molybdenum target mammography, ultrasound imaging, and magnetic resonance imaging (MRI) [ 6 – 8 ]. Due to their different imaging principles, each examination method has its shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to present study, ElSaid et al [20] , also found US elastography to be comparable to MRI with respect to accuracy (84%) and did not find much difference in sensitivity and specificity of two techniques (84% vs 88% and 84% vs 80%). Song et al also found the sensitivity and specificity of elastography (94.3% and 85.7%) to be too close to that of MRI (96.2% and 91.4%) [29] . In their study, Parajuly et al [30] , reported a higher sensitivity and specificity of conventional USG (91.8% and 84.8%).…”
Section: Discussionmentioning
confidence: 97%